Human Follicular Fluid, Clinical Use of Proteomics Analysis in Identification of Infertility - Gairola, Nidhi; Deorari, Mahamedha; Jakhmola, Vikash; Sircar, Reema; Chitme, Havagiray R (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: In present situation infertility is one of the chief problem for reproductive couples due to multiple factors including lifestyle. Infertility is thought to be caused by both male and female factors in 27 percent of cases, with 15 percent of cases being idiopathic. Assisted reproductive technologies are used by these couples to overcome the problems related to infertility, but the success rate of ART is appreciated by WHO if it reaches to 30%. About 70% non-successful ART is due to the fact that molecular mechanism of human reproductive system is poorly understood. Materials and Methods: A systematic review was carried out using which pubmed, sciencedirect, scifinder, and google scholar databases. We followed standard criterion of inclusion and exclusion recommended by Cochrane review system. Information collected from the selected articles were compared and summarized in tables and Figures. Results: Proteomics is a promising approach for identifying possible biomarkers for infertility treatment and management. The use of OMICS technology to develop diagnostic and therapeutic techniques to increase the efficacy of ART is critical. Tandem mass spectrometry (LCMS/ MS) is used to identify peptides in proteins. Using advance proteomics tools such as SELDI-TOF, MALDI-TOF stressing the importance of protein in pregnancy maintenance and fertilization. Conclusion: We conclude from this study that using proteomics analysis can help in identifying potential biomarkers which can be used in the field of diagnostic and therapeutic of infertility. Further serious and extensive research is very much required in this field of research.
Keywords: Infertility; Assisted reproductive technologies; Proteomics; Therapeutic; Management